ANALISIS PERAN KEAMANAN DAN KUALITAS LAYANAN DIGITAL MOBILE BANKING TERHADAP KEPUASAN NASABAH PADA PT BANK PEMBANGUNAN DAERAH BALI - Ni Kadek Nita Permatasari; Kadek Cahya Dewi; Putu Adriani Prayustika (Berajah Journal, 2026)
In the banking sector, digital transformation has introduced mobile banking service innovations that allow the public to conduct financial transactions anytime and anywhere without having to visit a bank branch in person. This study aims to determine the partial and simultaneous effects of digital service security and digital service quality on customer satisfaction at PT Bank Pembangunan Daerah Bali in the Denpasar City and Badung regions. The study uses a quantitative method with a sample of 204 respondents. Analysis techniques include validity tests, reliability tests, classic assumption tests, multiple linear regression analysis, correlation analysis, the coefficient of determination, F-test, and t-test. The results show that all instruments are valid (r calculated > 0.361) and reliable, with Cronbach's Alpha values of 0.962 for digital service security, 0.954 for digital service quality, and 0.956 for customer satisfaction. The regression model meets the classic assumptions with a normality test significance value of 0.200 (>0.05). Correlation analysis shows a strong relationship (R = 0.737), while the Adjusted R Square value of 0.538 indicates that 53.8% of the variation in customer satis faction is explained by the two independent variables. The t-test results show that digital service security (t = 6.242; Sig. = 0.000) and digital service quality (t = 7.723, Sig. = 0.000) have a significant positive effect on customer satisfaction. The F-test yields a value of 119.318 (Sig. = 0.000), meaning that both variables simultaneously have a significant positive effect.